2016
DOI: 10.1155/2016/6492953
|View full text |Cite
|
Sign up to set email alerts
|

In VitroandIn VivoEvaluation of Niosomal Formulation for Controlled Delivery of Clarithromycin

Abstract: The present study was focused on formulating and evaluating clarithromycin (CLR) containing niosomal formulation for in vitro and in vivo pharmacokinetic behavior. Niosomal formulations (empty and drug loaded) were prepared by using different ratio of surfactant (various Span grades 20, 40, 60, and 80) and cholesterol by thin film hydration method and were evaluated for in vitro characteristics, stability studies, and in vivo study. Dicetyl phosphate (DCP) was added to the niosomal formulation. Various pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 28 publications
3
43
0
1
Order By: Relevance
“…It is clear from the results obtained that the niosomes have shown a minimum drug loss at refrigerated condition and fairly high retention of drug inside the vesicles was observed these results were concordant to Asthana et al (2016) [5]. At this low temperature condition only 2.797 % of drug was lost as compared to storage at 25 °C and 37 °C which led to 4.113 % and 5.125 % drug loss respectively at the end of 35 d results shown in (table 6).…”
Section: Drug Leakage Studysupporting
confidence: 74%
See 2 more Smart Citations
“…It is clear from the results obtained that the niosomes have shown a minimum drug loss at refrigerated condition and fairly high retention of drug inside the vesicles was observed these results were concordant to Asthana et al (2016) [5]. At this low temperature condition only 2.797 % of drug was lost as compared to storage at 25 °C and 37 °C which led to 4.113 % and 5.125 % drug loss respectively at the end of 35 d results shown in (table 6).…”
Section: Drug Leakage Studysupporting
confidence: 74%
“…It was clearly observed from the results that the mean vesicle size of niosomes containing span 20 were found to be higher as compared to other niosomal formulations containing span 40,60 and 80. The vesicle size of niosomal formulation were obtained in the range of 160.1±69.7 nm to718.7±749.9 nm (given in table 3) The vesicle size of niosomes decreased consistently from span 20 to span 80 and are found in the following order-span 20>span 40>span60>span 80 which was in conformance with Asthana et al (2016) [5].…”
Section: Vesicle Size Zeta Potential and Polydispersity Indexmentioning
confidence: 55%
See 1 more Smart Citation
“…It is worth noting that the physical stability was performed only at refrigerator temperature, as we found that storing the niosomes at room temperature was proven to negatively affect their stability, due to lowered hydrophobic part rigidity at higher temperature [52].…”
Section: Stability Studiesmentioning
confidence: 98%
“…When dispersed in an appropriate solvent, gelling agents form a colloidal network structure. 9,10 Lipophilic and hydrophilic drugs can be entrapped in proniosomes either in aqueous layer or in vesicular membrane, which produced chemically and physically stable vesicles having low toxicity because of their non-ionic nature .…”
Section: Introductionmentioning
confidence: 99%